Implementasi Peraturan Daerah No 1 Tahun 2022 tentang Penyelenggaraan Perizinan Berusaha Berbasis Risiko - Hayani, Yuma; Rispawati, Rispawati; Sawaludin, Sawaludin; Yuliatin, Yuliatin (Journal of Civic Education, 2025)
The purpose of the following study is to determine the implementation of the Mataram City Regional Regulation No. 1 of 2022 related to the implementation of risk-based business licensing, especially in the trade sector, culinary type MSMEs and obstacles in the implementation of Mataram City Regional Regulation Number 1 of 2022 concerning the implementation of risk-based business licensing. Data collection methods were carried out to collect research data, namely through interviews, observation, and documentation. The study was conducted in the city of Mataram, with research samples including the business licensing service section and the head of the UMKM of Kelurahan Rembiga. The sample selection was carried out through purposive sampling technique, namely by determining several indicators according to certain criteria. The results of research related to the implementation of regional policies related to the implementation of risk-based business licensing in the city of Mataram show that the implementation of regional regulations in terms of providing services to business actors through online risk-based with the Online Single Submissions (OSS) site has achieved good synergy. Reviewed from the service implementation mechanism, implementation results, implementation evaluation and using the theory of public policy implementation based on George C. Edward III. In addition, it will also be examined regarding a number of obstacles faced in the implementation of risk-based business licensing services by public officials, namely DPMPTSP as the policy organizer and its staff.